"Opening Pandora's Box: Will the Return of Cultural Heritage Objects to Their Country of Origin Empty Western Museums?". Issue 6 (28th October 2021) - Losson, Pierre
Abstract: The fear of setting a precedent is a much-rehearsed argument used by Western museums to refuse the return of cultural heritage objects to their country of origin. After proposing to consistently distinguish among returns, restitutions, and repatriations as distinct phenomena, the article details three reasons that contradict this fear of setting a precedent: as each case is historically situated, one agreement is not easily transposable to other cases; the current practice of returns does not suggest that massive transfers are looming; and, most importantly, there is no will or plan, among experts and political authorities in claiming countries, to ask for massive returns. In turn, the fear of setting a precedent does open questions about the future museums: are universal museums at risk of disappearing? The museum as an institution is hardly at risk, as objects returned to another country will continue to live in the world of museums. Western universal museums should see return claims as an opportunity to rethink their mission and relations with other museums worldwide rather than a threat.